Clinical significance of assessing autoantibody level in diagnostics of early and late fetal growth retardation - I. V. Ignatko; D. I. Yakubova; A. D. Megrabyan; E. V. Timokhina (Акушерство, гинекология и репродукция)
Aim: to analyze diagnostic potential of early and late fetal growth retardation (FGR) based on examining significance of serum autoimmune antibody (АВ) level.Materials and Methods. A single center prospective cohort comparative study included 98 pregnant women: 79 with FGR (main group I) and 19 with physiological course of pregnancy (comparison group II). Depending on the time of manifestation, pregnant women with FGR were divided into 2 subgroups: early FGR (subgroup IA, n = 41) and late FGR (subgroup group IB, n = 38). All patients underwent venous blood sampling to determine the serum autoimmune AB level against 12 human self-antigens using the ELI-P-Test: for human chorionic gonadotropin antigen (hCG), DNA, β2-glycoprotein (β2-GP), collagen, fragment crystallizable of immunoglobulin G (Fc-IgG), insulin, thyroglobulin, S100 protein, surface antigen of germ cell and prostate (Spr), thrombocyte membrane protein (TrM), antineutrophil cytoplasmic antibodies (ANCA), and membrane antigen of glomerular cells (KiMS). Venous blood sampling was carried out in the main group at the time of establishing FGR diagnosis (the third trimester of pregnancy in all cases): early manifested FGR – 29 [28; 31] weeks, late manifested FGR – 5 [33; 36] weeks, comparison group II – 33 [32; 35] weeks.Results. To diagnose early FGR, the level of the following autoimmune АВ was shown to be significantly increased against hCG, collagen, S100 protein, TrM, ANCA, KiMS (p = 0.037; р = 0.001; р = 0.013; р = 0.005; р = 0.003; p < 0.001, respectively), whereas late FGR was diagnosed based on measuring АВ against DNA, collagen, insulin, S100 protein (p = 0.002; p = 0.003; p = 0.010; p < 0.001, respectively).Conclusion. Detecting autoimmune antibodies has shown its informative importance in pregnant women with FGR, so that changes in serum autoantibody level may serve as a laboratory marker of early and late FGR.